2024
DOI: 10.31557/apjcp.2024.25.3.793
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Knowledge, Attitude, and Practice Regarding Human Papilloma Virus Vaccination at the Community Level in India: A Systematic Review and Meta-analysis

Debkumar Pal,
Bimal Sahoo,
Manish Taywade
et al.

Abstract: Background: Effective vaccines for the prevention of cervical cancers are available in India. The existing knowledge and attitude regarding the Human Papillomavirus (HPV) vaccine varies widely among available studies. Our study aimed to estimate pooled prevalence related to knowledge, attitude, and practice of HPV vaccination in India. Methodology: We conducted systematic searches in PUBMED, EMBASE, CINHAL, PROQUEST, and Cochrane Library databases using database-specific search strategies. The random effects m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Overall, Pal et al [1] review could guide clinical practitioners and policymakers to plan strategies to improve HPV vaccine uptake in India. However, the review should be carefully interpreted due to concerns related to literature screening and the combination of the studies through meta-analysis, which impedes the review's reproducibility and validity of findings.…”
Section: Methodological Assessment Of a Review Of Knowledge Attitude ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, Pal et al [1] review could guide clinical practitioners and policymakers to plan strategies to improve HPV vaccine uptake in India. However, the review should be carefully interpreted due to concerns related to literature screening and the combination of the studies through meta-analysis, which impedes the review's reproducibility and validity of findings.…”
Section: Methodological Assessment Of a Review Of Knowledge Attitude ...mentioning
confidence: 99%
“…It is important that the review is as rigorous and as fully reported as possible if the evidence from the review is incorporated into clinical practice. We read, with great interest, the systematic review and meta-analysis by Pal et al (2024) titled 'Evidence of Knowledge, Attitude, and Practice Regarding Human Papilloma Virus Vaccination at the Community Level in India: A Systematic Review and Meta-Analysis' that attempts to give information on the prevalence of knowledge, attitude, and practice of HPV vaccination in the Indian population. [1].…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations